Design of Controlled Pre-Split Blasting in a Hydroelectric Construction Project - Younes Tahir; Imad Kadiri; Saïf Ed-dîn Fertahi; Mohammed El Youbi; Rachid Bouferra; Rachid Agounoun; M. Dlimi (Civil Engineering Journal, 2023)
Geologic conditions and design requirements around upstream Nachtigal Falls, in Cameroon, for the hydroelectric construction project on the Sanaga River dictated close control of blasting procedures with very precise geometry to obtain safe and economical excavation lines. Various techniques of pre-split blasting were used in the initial stage of all major excavations. Hole diameters for pre-splitting were 89 mm, and hole spacing ranged from 0.8 to 1m. Explosive charges varied from 1 to 7 kg per hole, and the detonating cord linear charge ranged from 12 to 60g. The contour blasting technique is aimed at controlling overbreak and improving remaining slope stability. Over-break or over-excavation needs to be controlled since its occurrence compromises the operations in terms of safety (instability in the remaining slope; loosening rocks that increase the risk for operational people; an irregular free face for subsequent blasting); and costs (need for reinforcement of the remaining rock structure through costly sustainment systems; increase in concrete volumes in civil works). This paper discusses in detail the design and field implementation of pre-split blasts successfully carried out to achieve clean vertical walls in moderately dipping, though complexly sheared and jointed gneiss. Based on the results of the experiments, we were able to design a pre-splitting pattern both experimentally and in a very cost-effective manner. It is felt that the methods developed on this project could have useful applications on other major construction projects. Doi: 10.28991/CEJ-2023-09-03-05 Full Text: PDF